A Concept Analysis of Dependence Using Rodgers' Evolutionary Method. (4th May 2021) - Lingerfelt, Carrie N.; Hutson, Sadie P.
Abstract: The concept of dependence covers a broad range of experiences. Many health-related professions, including nursing, use the concept in the context of substance use and addiction; however, the use of the concept is often confusing and lacks distinct boundaries. Researchers and theorists in nursing require conceptual clarification and definition because it helps ensure effective theory development and operationalization of the concept as a research variable. A concept analysis using Rodgers' Evolutionary Method is presented, resulting in a revised definition of dependence, as it relates to substance use disorders and addiction. This analysis and resultant definition are timely to the nation's opioid use disorder epidemic. Surrogate terms, related concepts, attributes, assumptions, consequences, and a model case of dependence support the assertion for a change in terminology and culminate with clarification of a new definition for use in nursing.